Agronomic characteristics of corn hybrids for silage production in the State of Mato Grosso, Brazil - doi: 10.4025/actascianimsci.v35i1.15592 (Acta Scientiarum. Animal Sciences, 2012)
The experiment was conducted at the Experimental Farm of the Federal University of Mato Grosso in the municipality of Santo Antônio do Leverger, State of Mato Grosso, Brazil to evaluate the agronomic characteristics of corn hybrids in the cultivation of second crop for silage production. The experimental design was carried out with randomized blocks with 23 treatments (hybrids) and three replications. Corn hybrids from different seed companies and recommended for the midwestern region of Brazil, were used. The agronomic traits were: stem diameter (cm), plant height and ear insertion (m); yield of green matter (ton. ha-1), percentage of spike, stem and leaves in green mass; ear productivity (ton. ha-1), dry matter content of stem + leaf and whole plant. Hybrids BF 9304, DKB 370, 177 DKB, BF 9534, BF 9417, AG 5020, BE 9701, P 3021 and P 30F98 had the highest production of green matter, plant height and spike insertion. The hybrid BF 9304 was also prominent for spike percentage (50.55%).